Keragaman Virulensi dan Konstruksi Molekuler Virus Tungro pada Padi dari Daerah Endemis - Praptana, R. Heru; Sumardiyono, Y. B.; Hartono, Sedyo; Trisyono, Y. Andi; Widiarta, I Nyoman (Jurnal Penelitian Pertanian Tanaman Pangan, 2014)
Tungro is an important disease of rice, constraining to the rice production in Indonesia. Tungro is caused by the infection of two different viruses namely tungro bacilliform virus (RTBV) and tungro spherical virus (RTSV). Both viruses are only transmitted by green leafhoppers, especially Nephotettix virescens in a semipersistent manner. The variation of tungro viruses from different areas had been reported, and there is a specific relationship between resistance variety and tungro virus isolate. It is important therefore, to study the virulences and the genetic diversities of tungro viruses derived from the endemic areas in Indonesia. This study was aimed to identify the virulence and the molecular diversity of tungro viruses from endemic areas in Indonesia. Susceptible variety TN1 was used in the study. Surveys and collection of the infected plants and green leafhoppers were conducted in some tungro endemic areas, including: West Java, Central Java, Yogyakarta, Central Sulawesi, West Sulawesi, South Sulawesi, Bali and West Nusa Tenggara. Artificial virus transmission using test tube method was used in the virulence test. Green leafhoppers caught from the field were used as vector transmitters. The virulence of tungro viruses was determined based on diseases indexes (DI). Results showed that the virulence of tungro viruses varied among region in the endemic areas in Indonesia. The Central Java virus isolate was the most virulence; however, not all isolates from endemic areas in the island of Java were more virulent than those from outside of Java. The presence of RTBV and RTSV was detected in the infected TN1 plants. The existences of molecular diversities of tungro viruses from the endemic areas were observed. The relationship between combination of DNA bands of RTBV and RTSV with the virulence in endemic areas outside of Java was more complex than it was in West Java and Central Java. The molecular diversities of tungro viruses were not correlated with the geographic difference of the endemic areas, nor with the virulences.